Natural mycotoxin contamination of maize (Zea mays L.) in the South region of Brazil. (March 2017) - Oliveira, Maurício S.; Rocha, Alexandre; Sulyok, Michael; Krska, Rudolf; Mallmann, Carlos A.
Abstract: The natural co-occurrence of fungal metabolites in maize samples from the South region of Brazil was studied using an LC-MS/MS based multi-mycotoxin method. All maize samples (n = 148) were contaminated with fumonisin B1 (FB1 ) and fumonisin B2 (FB2 ). Aflatoxin B1 (AFB1 ) and aflatoxin G1 (AFG1 ) were detected in 38 and 11 samples, respectively, while zearalenone (ZEN) and deoxynivalenol (DON), which were first regulated in 2014, were found in 110 and 71 samples, respectively. Apart from regulated mycotoxins, a broad range of non-regulated metabolites, from Aspergillus, Fusarium, Alternaria, Penicillium and other microbes, were also detected in maize sample. Fusarin C, a possible carcinogenic compound to humans, produced by Fusarium species and not addressed by Brazilian legislation, was detected in 54.2% of maize samples. All analysed maize samples were found to be contaminated by at least ten different metabolites, with the largest number of metabolites found in the same sample being 51. Highlights: The co-occurrence of mycotoxins in maize samples from Brazil was noted. Fumonisins B1 and B2 were detected in all samples. Fusarin C was detected in more than half maize samples analysed. Aspergillus, Fusarium, Alternaria, Penicillium and bacterial metabolites were detected.